Optimization of the Duration of the Administration of Mesenchymal Stem Cells Wharton’s Jelly to the Level of Matrix Metalloproteinase-1 and Transforming Growth Factor-β in Osteoarthritis Rat Model - Endrinaldi, Endrinaldi; Ali, Hirowati; Tofrizal, Tofrizal; Asterina, Asterina; Elmatris, Elmatris; Yarni, Sisca Dwi (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Mesenchymal Stem Cell Wharton’s Jelly (MSC-WJ) is promising candidates for osteoarthritis (OA) therapy since they have chondrogenic potential and the ability to form the extracellular matrix. AIM: This study aimed to determine the effect of the time giving MSC-WJ on bioactive markers of osteoarthritis. METHODS: The osteoarthritis rat model was treated by intra-articular injection with MSC-WJ and α _MEM as a control. Four and 8 weeks later performed a histological analysis of cartilage and the determination of the levels of Matrix Metalloproteinase-1(MMP-1) and Transforming growth factor β1 (TGF-β1) in serum by ELISA. RESULTS: The results showed that administration of MSC-WJ showed improvement in the histological picture of knee joints in experimental animals characterized by an increase in cartilage thickness on the joint surface. The administration of MSC-WJ showed a tendency to decrease MMP-1 serum levels of OA rats treated for 8 weeks, although statistically did not show a significant difference. Whereas, administration of MSC-WJ showed a decrease in serum levels of TGF-β1 OA rat treated for 8 weeks. CONCLUSION: MSC-WJ can repair damaged knee OA cartilage tissue. The administration of MSC-WJ can reduce serum levels of TGF-β1 OA rats treated for 8 weeks.